Nonlinear error correction and the efficient market hypothesis: The case of German dual-class shares - Jörg Breitung; Christian Wulff (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
The efficient market hypothesis implies that asset prices cannot be cointegrated. On the other hand, arbitrage processes prevent prices of fundamentally related assets from drifting far away. An attractive model that reconciles these two conflicting facts is the nonlinear error correction mechanism (ECM). Such a process tolerates small deviations from the long run relationship. For more substantial deviations, an effective adjustment process pushes the diverging prices towards their fundamental relationship. In this paper parametric and nonparametric techniques are employed to investigate the ECM between prices of voting and non-voting stocks. Despite its intuitive appeal, we find little evidence for a nonlinear relationship between German dual-class shares. Only in 4 out of 12 cases, the threshold ECM yields a substantial improvement of fit. In other cases, the evidence for nonlinearity is rather weak and the threshold ECM fails to outperform the linear model.
urn:nbn:de:kobv:11-10046567
Keywords: C22; C51; 330